Lower-Extremity Pseudomyogenic Hemangioendothelioma on Bone Scintigraphy and PET/CT. (May 2017) - Krebs, Simone; Monti, Serena; Lewis, Natasha; Luciano, Alessandro; Rastrelli, Lapo; Mannelli, Lorenzo
Abstract : Abstract: An otherwise healthy 33-year-old man presents with new pain involving the right leg. Radiographs of the femur showed scattered lucent lesions. An MRI of the knee demonstrated nonspecific cortical-based lesions. Biopsy confirmed pseudomyogenic hemangioendothelioma. MDP bone scan and 18 F-FDG PET/CT were obtained to evaluate for extent of disease demonstrating disease limited to the bone of the right leg. Interestingly, the FDG and MDP uptake and CT appearance of the disease were not entirely concordant, with some lesions being lytic on CT and associated with FDG and MDP uptake, other lesions being CT silent and either MDP or FDG avid.